Survival Rate of Chronic Obstructive Pulmonary Disease Patients with Type II Respiratory Failure at Haji Adam Malik Hospital - Nahrisyah, Putri; Syahrani, Fajrinur; Tarigan, Amira Permatasari; Ashar, Taufik (CoinReads Media Prima, 2024)
Introduction: Chronic obstructive pulmonary disease is associated with acute exacerbations that can lead to respiratory failure and as major cause of morbidity and mortality worldwide. The Aim of study was to explore survival rate of COPD patients with type II respiratory failure Methods: Observational research with retrospective cohort design using data from medical records of chronic obstructive pulmonary disease patients with type II respiratory failure treated at H. Adam Malik General Hospital Medan for 10 months from November 2021 to September 2022. Analyzed of independent and dependent variables used Chi Square test. To obtain most dominant independent variable that influence dependent variable, a multiple logistic regression test is used. Results: There were 21 patients (50%) who alived until end of research but also 21 deaths occured. Survival rate was 50% with a median survival time 14 days (CI 95%: 7.178-20.822 days). Survival rate of COPD patients with type II respiratory failure who do not routinely received therapy was 16.7% with a median survival time 4 days (CI 95%: 42.962-5.039). Survival rate of COPD patients with type II respiratory failure who routinely received therapy was 75%. Based on log rank test, there was a significant difference median length of life between patients who did not and who routinely received therapy (p <0.001). Conclusion: The survival rate in COPD patients who regularly use inhaler therapy is significantly higher than patients who do not routinely use inhaler therapy.